2018
DOI: 10.3389/fpsyg.2018.00741
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanisms of Transcranial Magnetic Stimulation (TMS): How Brain State and Baseline Performance Level Determine Behavioral Effects of TMS

Abstract: The behavioral effects of Transcranial Magnetic Stimulation (TMS) can change qualitatively when stimulation is preceded by initial state manipulations such as priming or adaptation. In addition, baseline performance level of the participant has been shown to play a role in modulating the impact of TMS. Here we examined the link between these two factors. This was done using data from a previous study using a TMS-priming paradigm, in which, at group level, TMS selectively facilitated targets incongruent with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…We argue that the high specificity of our facilitation effect, selectively observed with increasing task demands in the congruent condition, argues against the unspecificity hypothesis. Rather, we believe that our findings indicate a specific facilitation effect best explained within the state-dependency framework [ 74 , 75 ]. Within this framework, it is argued that the direction and strength of an rTMS-induced effect strongly depends on the task-induced brain state and might thus either result in inhibition or facilitation of task performance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We argue that the high specificity of our facilitation effect, selectively observed with increasing task demands in the congruent condition, argues against the unspecificity hypothesis. Rather, we believe that our findings indicate a specific facilitation effect best explained within the state-dependency framework [ 74 , 75 ]. Within this framework, it is argued that the direction and strength of an rTMS-induced effect strongly depends on the task-induced brain state and might thus either result in inhibition or facilitation of task performance.…”
Section: Discussionmentioning
confidence: 95%
“…The induced activity might be synchronized with the ongoing relevant signal, thereby rendering the signal stronger and providing an “optimal” level of noise for a specific task or process, which might explain the observed facilitation effect in several studies of cognition [ 73 ], including the present one. Moreover, factors like stimulation intensity, time point of stimulation, and task difficulty have been shown to affect behavioral outcome, particularly in online rTMS paradigms like the one we used [ 74 , 75 ]. Consequently, the impact of an rTMS-induced perturbation might change with varying task conditions and complexity [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, researchers will adjust stimulation intensity based upon an individual's resting or active motor threshold (RMT, AMT; Ngomo et al, 2012), which is defined as the minimal stimulator intensity needed to induce a muscle evoked potential in 5 out of 10 occurrences in either a relaxed (RMT) or actively engaged muscle (AMT). Prior work has found evidence that low (below) and high (above) stimulation intensities mirror facilitatory vs. inhibitory neural activity that is also associated with enhancements vs. decrements in behavioral outcomes (Silvanto et al, 2018). In addition, recent findings have shown that the effects of stimulation intensity on cortical excitability also may interact with specific frequencies, which in turn can lead to divergent effects on cognitive performance (Chung et al, 2018).…”
Section: Principles Of Rtms and Episodic Memory That Are Important Fomentioning
confidence: 99%
“…Another possible explanation for the non-significant effects of combined protocols can be the high intensity (80%-100% of rMT) of HF rTMS protocols used in our study, which might contribute to the state-dependency of rTMS effects, as proposed by Silvanto et al (2017) for online-TMS-approaches [44]. According to their model, high-intensity stimulation might lead to inhibition of both task-relevant and irrelevant (noisy) neural activity, diminishing the resulting rTMS effects compared to mid-and low-intensity rTMS [45]. Chung et al (2018) have also shown that only mid-intensity, but not low-or high-intensity stimulation over the left DLPFC, demonstrated a significant effect on TMS-evoked potentials measured by TMS-EEG [18].…”
Section: Discussionmentioning
confidence: 85%